NOTARY LIABILITY OVER THEIR INVOLVEMENT IN DOCUMENT FALSIFICATION CRIME - Anggraeny, Isdian; Tongat, Tongat (Varia Justicia, 2020)
The presence of a notary in the Association of legal Communities is significant. Nevertheless, in carrying out its role and function, the Notary is very vulnerable in the vortex of deed against the law. Although in many instances, the public Notary can not be held accountable for the unlawful acts, in some cases, the Notary is unable to circumvent his involvement. This article presents two issues related to notary involvement in unlawful acts, especially the criminal offense. Each of these is: first, how is the form of notary involvement in criminal acts of document falsification? Secondly, can the public Notary be held accountable for his involvement in criminal acts of document falsification? This research was conducted through normative legal research. The results show that there are many forms of notary involvement in criminal acts of document counterfeiting. Secondly, the Notary may be held accountable and may be asked for criminal liability because of his involvement in criminal acts of document falsification.